Hibiscus syriacus Extract from an Established Cell Culture Stimulates Skin Wound Healing. (27th November 2017) - di Martino, O.; Tito, A.; De Lucia, A.; Cimmino, A.; Cicotti, F.; Apone, F.; Colucci, G.; Calabrò, V.
Abstract : Higher plants are the source of a wide array of bioactive compounds that support skin integrity and health. Hibiscus syriacus, family Malvaceae, is a plant of Chinese origin known for its antipyretic, anthelmintic, and antifungal properties. The aim of this study was to assess the healing and hydration properties of H. syriacus ethanolic extract (HSEE). We established a cell culture from Hibiscus syriacus leaves and obtained an ethanol soluble extract from cultured cells. The properties of the extract were tested by gene expression and functional analyses on human fibroblast, keratinocytes, and skin explants. HSEE treatment increased the healing potential of fibroblasts and keratinocytes. Specifically, HSEE significantly stimulated fibronectin and collagen synthesis by 16 and 60%, respectively, while fibroblasts contractility was enhanced by 30%. These results were confirmed on skin explants, where HSEE accelerated the wound healing activity in terms of epithelium formation and fibronectin production. Moreover, HSEE increased the expression of genes involved in skin hydration and homeostasis. Specifically, aquaporin 3 and filaggrin genes were enhanced by 20 and 58%, respectively. Our data show that HSEE contains compounds capable of stimulating expression of biomarkers relevant to skin regeneration and hydration thereby counteracting molecular pathways leading to skin damage and aging.